Characterization of Lipase Produced by Thermophilic Fungi Isolated From Pome - Abd. Samad, Mohd. Yusoff (1990)

(untitled)
A plate assay to determine lipase activity was developed. Tween 80, used as a substrate with Victoria Blue B as the indicator seemed to be a reliable technique. Lipolytic activity was determined by the formation of the zone of intensification of the indicator colour after 24 hr. Intensity of the colour developed was greater than that of triolein dye system and clearer than the hydrolysis zone of tributyrin plate. Test using a commercial enzyme and growth media containing lipolytic activity showed that the zone of intensification increased with increased lipolytic activity. A linear relationship could be seen when log enzyme concentration was plotted against the diameter of zone of intensification. Using this technique primary screening of lipolytic microorganisms could be conducted using the formation of zone of intensification around the colonies and mycelia. Five fungi showing lipolytic activity on plate were isolated using plate assay. However, using broth culture only one fungus was found to produce lipase. The fungus was identified as Rhizopusrhizopodiformis, (strain S1 and S2). Strain S1 was found to produce maximum lipase yield in the basal medium containing of peptone and glycerol.